Analisis Fenomena Harga Minyak Goreng di Indonesia dan Dampaknya terhadap Sektor Penyediaan Makan Minum - Adin Nugroho; Prientananda Ghina Salsabila (Politeknik Statistika STIS, 2022)
The increase in global CPO prices had pushed up the prices of its derivative products, including cooking oil that has been one of the basic need of Indonesian people. The increase in cooking oil prices at the end of 2021 to June 2022 that reached 25.400 rupiahs might certainly have impact on sectors that were directly related to it, such as the food and beverages service activities. Therefore, this study was conducted to analyze the factors that influenced the increasing cooking oil prices and its impact on the food and beverage supply sector. This research used data of cooking oil price, CPO production, CPO consumption, CPO export, CPO price, and CPI of food and beverage in Indonesia with the period of Januari 2020 – June 2022. The methods that were used in this research included Autoregressive Integrated Moving Average (ARIMA), Principal Component Analysis (PCA), Analisis Faktor, dan Autoregressive Distirbuted Lag (ARDL). In the result of this study, it was shown that supply and demand factors had a significant influence toward the changes in cooking oil prices not in the current period, but in the following period instead. On the other hand the increasing cooking oil prices, which was included in market pressure factor, had a 0,723 units significant and parallel impact on the changes of Consumer Price Index (CPI) for Food and Beverage Service Activities in the same period.